Forcing Subsets of Connected Co-Independent Hop Domination in the Edge Corona and Lexicographic Product of Graphs (European Journal of Pure and Applied Mathematics, 2022)
This study deals with the forcing subsets of a minimum connected co-independent hop dominating sets in graphs. Bounds or exact values of the forcing connected co-independent hop domination numbers of graphs resulting from some binary operations such asedge corona and lexicographic product of graphs are determined.Some main results generated in this study include: (a) characterization of the minimum connected co-independent hop dominating sets; and (b) characterization of the forcing subsets for these types of sets.
Keywords: Forcing subsets; connected co-independent hop; domination; co- independent set